The ectomycorrhizal basidiomycete Laccaria bicolor releases a GH28 polygalacturonase that plays a key role in symbiosis establishment. Issue 6 (17th January 2022) - Zhang, Feng; Labourel, Aurore; Haon, Mireille; Kemppainen, Minna; Da Silva Machado, Emilie; Brouilly, Nicolas; Veneault‐Fourrey, Claire; Kohler, Annegret; Rosso, Marie‐Noëlle; Pardo, Alejandro; Henrissat, Bernard; Berrin, Jean‐Guy; et al.
Summary: In ectomycorrhiza, root penetration and colonization of the intercellular space by symbiotic hyphae is thought to rely on the mechanical force that results from hyphal tip growth, enhanced by the activity of secreted cell‐wall‐degrading enzymes. Here, we characterize the biochemical properties of the symbiosis‐induced polygalacturonase LbGH28A from the ectomycorrhizal fungus Laccaria bicolor . The transcriptional regulation of LbGH28A was measured by quantitative PCR (qPCR). The biological relevance of LbGH28A was confirmed by generating RNA interference (RNAi)‐silenced LbGH28A mutants. We localized the LbGH28A protein by immunofluorescence confocal and immunogold cytochemical microscopy in poplar ectomycorrhizal roots. Quantitative PCR confirmed the induced expression of LbGH28A during ectomycorrhiza formation. Laccaria bicolor RNAi mutants have a lower ability to establish ectomycorrhiza, confirming the key role of this enzyme in symbiosis. The purified recombinant LbGH28A has its highest activity towards pectin and polygalacturonic acid. In situ localization of LbGH28A indicates that this endopolygalacturonase is located in both fungal and plant cell walls at the symbiotic hyphal front. These findings suggest that the symbiosis‐induced pectinase LbGH28A is involved in the Hartig net formation and is an important determinant for successful symbiotic colonization.